A Fe-Co-Ni nanoalloy, its preparation method and application
Patent Information
- Application Number
- CN202511873954.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-12
- Publication Date
- 2026-09-01
- Estimated Expiration
- 2045-12-12
AI Technical Summary
[0004]但到目前为止,具有六边形的中、高熵合金材料还未见报道
Smart Images

Figure CN121696386B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an Fe-Co-Ni nanomaterial, its preparation method, and its application, belonging to the field of functional materials technology. Background Technology
[0002] Metal alloys play an irreplaceable role in the development of human society and are widely used in daily life and industry.
[0003] Medium-entropy alloys are novel alloys composed of 3-4 main metallic elements in equal proportions. Their mixing entropy value (0.85-1.3R) falls between that of traditional alloys and high-entropy alloys, offering advantages in high strength, corrosion resistance, and cost. High-entropy alloys refer to multi-principal element alloy systems composed of five or more metallic elements in equiatomic or near-equiatomic ratios. The mixing entropy of high-entropy alloys is typically greater than 1.5R, thus thermodynamically tending to form solid solution phases with simple crystal structures (such as face-centered cubic or body-centered cubic). High-entropy alloys possess a series of unique structural characteristics and performance advantages, including the high-entropy effect, lattice distortion effect, hysteresis diffusion effect, and cocktail effect, thus exhibiting superior properties that are difficult for traditional alloys to possess simultaneously, such as enzyme-like activity, thermal stability, high strength, high hardness, excellent wear resistance, oxidation resistance, superparamagnetism, corrosion resistance, and radiation resistance. These characteristics make them promising for applications in aerospace, nuclear energy, high-temperature components, wear-resistant coatings, biomedicine, and many other fields.
[0004] However, no reports have been made of hexagonal medium- or high-entropy alloy materials to date. Summary of the Invention
[0005] This invention designs a Fe-Co-Ni nanoalloy. The alloy utilizes abundant and cost-effective metal chlorides as precursors, trioctylphosphine oxide (TOPO) as ligands, and ethanol and 1-octadecene (ODE) as mixed solvents to synthesize hexagonal nanoalloys at low temperatures using a wet chemical method. This method can synthesize 3- to 10-membered medium- and high-entropy alloys with broad application prospects. The synthesis is a precise process guided by organic ligands, involving multi-metal synergy, and encompassing nucleation, self-assembly, and anisotropic growth.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: A Fe-Co-Ni nanoalloy, characterized in that the nanoalloy is composed of three elements, iron, cobalt, and nickel, and one or more elements selected from manganese, copper, and zinc; the molar ratio of each element is equivalent; and the nanoalloy has a hexagonal HCP crystal structure.
[0007] Preferably, the nanocrystal size of the nanoalloy is 400~600nm; the nanoalloy is a two-dimensional nanosheet HCP single-phase structure, and the thickness of the nanosheet is 10~50nm.
[0008] This invention also provides a method for preparing Fe-Co-Ni nanoalloys, comprising the following steps: (1) Using chlorides or acetylacetones or acetates of iron, cobalt, nickel, manganese, copper and zinc as raw materials, weigh them according to the ratio and put them into a pressure-resistant bottle. Weigh trioctylphosphine oxide and put it into the pressure-resistant bottle. Then add anhydrous ethanol to obtain the first solution. (2) Add 1-octadecene to the first solution, treat the mixed solution with an ultrasonic machine, and obtain the second solution after the reaction solution is fully dissolved; (3) Place the second solution in an oil bath and heat it to 80°C for 5-30 minutes to allow the nano-alloy to grow crystal nuclei. Then, react it at 140-220°C for 20-60 minutes to allow the crystal nuclei to grow anisotropically into nano-medium and high-entropy alloys, thus obtaining the third solution. (4) Transfer the third solution to a centrifuge tube, wash, centrifuge, and collect the precipitate to obtain the Fe-Co-Ni nano-alloy.
[0009] The beneficial effects of adopting the above technical solution are as follows: TOPO is the key guiding factor for hexagonal formation, and ODE is a high-temperature protective agent; it is impossible to synthesize without replacing ODE with oleylamine. The metal elements used in this invention have relatively close atomic radii, and their synergistic growth can better form medium- and high-entropy nano-solid solutions, resulting in a greater synergistic effect.
[0010] Preferably, the volume molar ratio of the anhydrous ethanol, 1-octadecene, trioctylphosphine oxide, and the single element is 3~5 ml: 10 ml: 1 mmol: 1~2 mmol.
[0011] Preferably, the chloride, acetylacetone, or acetate salt has a purity of 99.5% or higher.
[0012] Preferably, in step (2), the mixed solution is treated with an ultrasonic machine for more than 30 minutes until the precipitate is completely dissolved.
[0013] Preferably, in step (3), the precipitate is washed with a mixed solution of ethanol:acetone:cyclohexane 1~2:1:1, centrifuged at 4000~6000 rpm for 5~10 minutes, the solution is discarded, and the precipitate is retained; the washing operation is repeated three or more times until the solution becomes clear and transparent, the precipitate is collected and stored in cyclohexane solution at 4℃.
[0014] The present invention also discloses the application of the above-mentioned nanoalloys in bioenzymes and high-temperature alloy devices.
[0015] Preferably, the bioenzyme has the ability to catalyze hydrogen peroxide and can promote the generation and removal of reactive oxygen species. The application is not for diagnostic or therapeutic purposes.
[0016] As can be seen from the above technical solution, compared with the prior art, the advantages of this invention are: the preparation method of medium- and high-entropy nanoalloys is mild and highly reproducible. The prepared nanoalloys have uniform size, approximately 600 nm, and a distinct crystal lattice. The reaction system uses non-precious metals, making it economical and environmentally friendly, and possessing good application potential in biocatalysis and high-temperature resistance. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0018] Figure 1 This is a transmission electron microscope (TEM) image of the high-entropy nanoalloy prepared in Example 1 of this invention.
[0019] Figure 2 This is a transmission electron microscope (TEM) image of the high-entropy nanoalloy prepared in Example 2 of this invention.
[0020] Figure 3 This is a scanning transmission electron microscope (STEM) image of the high-entropy nanoalloy prepared in Example 3 of this invention.
[0021] Figure 4 This is a transmission electron microscope (TEM) image of the high-entropy nanoalloy prepared in Example 4 of this invention.
[0022] Figure 5 This is an X-ray energy dispersive spectroscopy (EDS) image of the high-entropy nanoalloy prepared in Example 3 of this invention.
[0023] Figure 6 This study investigates the catalase-like enzyme activity of the high-entropy nanozyme prepared in Example 3 of this invention.
[0024] Figure 7 This is a transmission electron microscope (TEM) image of the product of Comparative Example 1 of this invention.
[0025] Figure 8 This is a transmission electron microscope (TEM) image of the product of Comparative Example 2 of the present invention. Detailed Implementation
[0026] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0027] Example 1: 1) Add ferric chloride, cobalt chloride, and nickel chloride to a pressure-resistant bottle in a molar ratio of 1:1:1; the molar mass of ferric chloride, cobalt chloride, and nickel chloride is 0.5 mmol each. Weigh 0.6 mmol of trioctylphosphine oxide (TOPO) and add it to the pressure-resistant bottle. Then add 2 ml of anhydrous ethanol to obtain the first solution. (2) Add 5 ml of 1-octadecene to the first solution, and treat the mixed solution with an ultrasonic machine for more than 30 minutes. After the reaction solution is fully dissolved, the second solution is obtained. (3) The second solution is placed in an oil bath and heated to 80°C for 10 minutes to allow the nano-alloy to grow crystal nuclei. Then it is reacted at 180°C for 30 minutes to allow the crystal nuclei to grow anisotropically into nano-medium-entropy alloys, thus obtaining the third solution. (4) Transfer the third solution to a centrifuge tube, wash with a 1:1:1 mixture of ethanol:acetone:cyclohexane, centrifuge at 5000 rpm for 10 minutes, discard the solution and keep the precipitate; repeat the washing operation three or more times until the solution becomes clear and transparent; collect the precipitate and store it in cyclohexane solution at 4°C.
[0028] Example 2: (1) Add the four compounds ferric chloride, cobalt chloride, nickel chloride and manganese chloride to a pressure-resistant bottle in a molar mass ratio of 1:1:1:1; the molar mass of ferric chloride:cobalt chloride:nickel chloride:manganese chloride is 0.5 mmol; weigh 0.6 mmol of trioctylphosphine oxide (TOPO) and add it to the pressure-resistant bottle, then add 2 ml of anhydrous ethanol to obtain the first solution; (2) Add 5 ml of 1-octadecene to the first solution, and treat the mixed solution with an ultrasonic machine for more than 30 minutes. After the reaction solution is fully dissolved, the second solution is obtained. (3) The second solution is placed in an oil bath and heated to 80°C for 10 minutes to allow the nano-alloy to grow crystal nuclei. Then it is reacted at 180°C for 30 minutes to allow the crystal nuclei to grow anisotropically into nano-medium-entropy alloys, thus obtaining the third solution. (4) Transfer the third solution to a centrifuge tube, wash with a 1:1:1 mixture of ethanol:acetone:cyclohexane, centrifuge at 5000 rpm for 10 minutes, discard the solution and keep the precipitate; repeat the washing operation three or more times until the solution becomes clear and transparent; collect the precipitate and store it in cyclohexane solution at 4°C.
[0029] Example 3: (1) Five compounds, namely ferric chloride, cobalt chloride, nickel chloride, manganese chloride and copper chloride, were added to a pressure-resistant bottle in a molar mass ratio of 1:1:1:1:1. The molar mass of ferric chloride:cobalt chloride:nickel chloride:manganese chloride:copper chloride was 0.5 mmol. 0.6 mmol of trioctylphosphine oxide (TOPO) was weighed and added to the pressure-resistant bottle. Then 2 ml of anhydrous ethanol was added to obtain the first solution. (2) Add 5 ml of 1-octadecene to the first solution, and treat the mixed solution with an ultrasonic machine for 30 minutes. After the reaction solution is fully dissolved, the second solution is obtained. (3) The second solution is placed in an oil bath and heated to 80°C for 10 minutes to allow the nano-alloy to grow crystal nuclei. Then, it is reacted at 180°C for 30 minutes to allow the crystal nuclei to grow anisotropically into a nano-high entropy alloy, thus obtaining the third solution.
[0030] (4) Transfer the third solution to a centrifuge tube, wash with a 1:1:1 mixture of ethanol:acetone:cyclohexane, centrifuge at 5000 rpm for 10 minutes, discard the solution and keep the precipitate; repeat the washing operation three or more times until the solution becomes clear and transparent; collect the precipitate and store it in cyclohexane solution at 4°C.
[0031] Example 4: (1) Six compounds, namely ferric chloride, cobalt chloride, nickel chloride, manganese chloride, copper chloride, and zinc chloride, were added to a mixed solution of ethanol and ODE. The molar ratio of ferric chloride:cobalt chloride:nickel chloride:manganese chloride:copper chloride:zinc chloride in the mixed solution was 1:1:1:1:0.5 mmol each, and 1:1. The solution was placed in a pressure-resistant bottle. 0.6 mmol of trioctylphosphine oxide (TOPO) was weighed and added to the pressure-resistant bottle. Then 2 ml of anhydrous ethanol was added to obtain the first solution. (2) Add 5 ml of 1-octadecene to the first solution, and treat the mixed solution with an ultrasonic machine with a power of 250 W for 30 minutes. After the reaction solution is fully dissolved, the second solution is obtained. (3) The second solution is placed in an oil bath and heated to 80°C for 10 minutes to allow the nano-alloy to grow crystal nuclei. Then, it is reacted at 180°C for 30 minutes to allow the crystal nuclei to grow anisotropically into a nano-high entropy alloy, thus obtaining the third solution.
[0032] (4) Transfer the third solution to a centrifuge tube, wash with a 1:1 mixture of ethanol and acetone, centrifuge at 5000 rpm for 10 minutes, discard the solution, and retain the precipitate; repeat the washing operation three or more times until the solution becomes clear and transparent. Collect the precipitate and store it in cyclohexane solution at 4°C.
[0033] The method of this invention prepares nanoscale medium- and high-entropy solid solutions using chlorides, acetylacetones, or acetates of iron, cobalt, nickel, manganese, copper, zinc, etc., as raw materials, in ethanol and ODE solvents, through a process of metal element electron loss driven by temperature and coordination effects.
[0034] Examples 1-4 yielded TEM or STEM images of medium- and high-entropy nanoalloys, as shown below. Figure 1-4 As shown. From Figure 1-4 It can be seen that medium- and high-entropy nanoalloys are hexagonal with a size of 400-600 nm. For example... Figure 5 As shown, ESD characterization of the high-entropy nanoalloy prepared in Example 3 indicates that it contains five elements: iron, cobalt, nickel, manganese, and copper. Figure 6 As shown, the high-entropy nanoalloy prepared in Example 3 exhibits good bio-enzyme-like activity.
[0035] The high-entropy nanoalloys prepared by the method of this invention exhibit excellent catalase activity. The activity study includes the following steps: (1) Disperse medium and high entropy nano-alloys in ultrapure water to a mass-volume concentration of 1 mg / mL, and treat with an ultrasonic machine for 10-30 minutes to obtain the fourth solution; (2) Take 10 μL of 1 mM hydrogen peroxide standard solution and add it to a centrifuge tube. Add 2.5 μL, 5 μL, 10 μL, 20 μL and 30 μL of 1 mg / mL high entropy nano-alloy material to each centrifuge tube respectively, and let the material react with the hydrogen peroxide standard solution for 20 minutes to obtain the fifth solution. (3) Prepare the sixth solution according to the hydrogen peroxide quantitative analysis kit (water compatible); (4) Take 200 μL of the sixth solution and add it to the corresponding well of the 96-well plate. After the fifth solution has reacted, take 20 μL of the fifth solution of different concentrations and add it to the corresponding 96-well plate. Set up three replicate wells for each concentration. (5) The absorbance at 595 nm was measured using an ELISA reader, and the data was finally processed to obtain the results. Figure 4 The data shown are for hydrogen peroxide removal efficiency.
[0036] Comparative Example 1 (1) Five compounds, namely ferric chloride, cobalt chloride, nickel chloride, manganese chloride, and copper chloride, were added to a mixed solution of ethanol and ODE. The molar ratio of ferric chloride:cobalt chloride:nickel chloride:manganese chloride:copper chloride in the mixed solution was 2:1:1:2:1, and the molar mass of copper chloride was 0.5 mmol. The solution was placed in a pressure-resistant bottle. 0.6 mmol of trioctylphosphine oxide (TOPO) was weighed and added to the pressure-resistant bottle, and then 2 ml of anhydrous ethanol was added to obtain the first solution. (2) Add 5 ml of 1-octadecene to the first solution, and treat the mixed solution with an ultrasonic machine with a power of 250 W for 30 minutes. After the reaction solution is fully dissolved, the second solution is obtained. (3) Place the second solution in an oil bath and heat it to 80°C for 10 minutes, then react it at 180°C for 30 minutes to obtain the third solution.
[0037] (4) Transfer the third solution to a centrifuge tube, wash with a 1:1:1 mixture of ethanol:acetone:cyclohexane, centrifuge at 5000 rpm for 10 minutes, and no precipitate can be obtained. Comparative Example 2 (1) Five compounds, namely ferric chloride, cobalt chloride, nickel chloride, manganese chloride and copper chloride, were added to a mixed solution of ethanol and ODE. The molar mass ratio of ferric chloride:cobalt chloride:nickel chloride:manganese chloride:copper chloride in the mixed solution was 1:1:1:1:1, and each was 0.5 mmol. The solution was placed in a pressure-resistant bottle. Without adding trioctylphosphine oxide (TOPO), 2 ml of anhydrous ethanol was added to obtain the first solution. (2) Add 5 ml of 1-octadecene to the first solution, and treat the mixed solution with an ultrasonic machine for 30 minutes. After the reaction solution is fully dissolved, the second solution is obtained. (3) Place the second solution in an oil bath and heat it to 80°C for 10 minutes, then react it at 180°C for 30 minutes to obtain the third solution.
[0038] (4) Transfer the third solution to a centrifuge tube, wash with a 1:1:1 mixture of ethanol:acetone:cyclohexane, centrifuge at 5000 rpm for 10 minutes, discard the solution, and retain the precipitate; repeat the washing operation three or more times until the solution becomes clear and transparent. Collect the precipitate and store it in cyclohexane solution at 4°C. Because TOPO was not added, hexagonal high-entropy nanoalloys could not be obtained.
[0039] Comparative Example 3 (1) Five compounds, namely ferric chloride, cobalt chloride, nickel chloride, manganese chloride, and copper chloride, were added to a mixed solution of ethanol and oleylamine. The molar ratio of ferric chloride:cobalt chloride:nickel chloride:manganese chloride:copper chloride in the mixed solution was 1:1:1:1:1, and the molar mass of copper chloride was 0.5 mmol. The solution was placed in a pressure-resistant bottle. 0.6 mmol of trioctylphosphine oxide (TOPO) was weighed and added to the pressure-resistant bottle, and then 2 ml of anhydrous ethanol was added to obtain the first solution. (2) Add 5 ml of oleylamine to the first solution and treat the mixed solution with an ultrasonic machine with a power of 250 W for 30 minutes. After the reaction solution is fully dissolved, the second solution is obtained. (3) Place the second solution in an oil bath and heat it to 80°C for 10 minutes, then react it at 180°C for 30 minutes to obtain the third solution.
[0040] (4) Transfer the third solution to a centrifuge tube, wash with a 1:1:1 mixture of ethanol:acetone:cyclohexane, and centrifuge at 5000 rpm for 10 minutes. Since 1-octadecene was replaced with oleylamine, no precipitate could be obtained. Comparative Example 4 (1) Five compounds, namely ferric chloride, cobalt chloride, nickel chloride, manganese chloride, and copper chloride, were added to a mixed solution of ethanol and ODE. The molar ratio of ferric chloride:cobalt chloride:nickel chloride:manganese chloride:copper chloride in the mixed solution was 1:1:1:1:1, and the molar mass of copper chloride was 0.5 mmol. The solution was placed in a pressure-resistant bottle. 0.6 mmol of trioctylphosphine oxide (TOPO) was weighed and added to the pressure-resistant bottle, and then 3 ml of anhydrous ethanol was added to obtain the first solution. (2) Add 5 ml of 1-octadecene to the first solution, and treat the mixed solution with an ultrasonic machine with a power of 250 W for 30 minutes. After the reaction solution is fully dissolved, the second solution is obtained. (3) Place the second solution in an oil bath and heat it to 80°C for 10 minutes, then react it at 180°C for 30 minutes to obtain the third solution.
[0041] (4) Transfer the third solution to a centrifuge tube, wash with a 1:1:1 mixture of ethanol: acetone: cyclohexane, and centrifuge at 5000 rpm for 10 minutes. Due to the increased amount of ethanol used in step (1), no precipitate can be obtained. The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on its differences from other embodiments. Similar or identical parts between embodiments can be referred to interchangeably. For the apparatus disclosed in the embodiments, since they correspond to the methods disclosed in the embodiments, the description is relatively simple; relevant parts can be referred to the method section.
[0042] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A Fe-Co-Ni nanoalloy, characterized in that, The nanoalloy is composed of three elements: iron, cobalt, and nickel, and zero or more elements selected from manganese, copper, and zinc; the molar ratio of each element is equal; the nanoalloy has a hexagonal HCP crystal structure. The preparation method of the nano-alloy includes the following steps: (1) Using chlorides or acetylacetones or acetates of iron, cobalt, nickel, manganese, copper and zinc as raw materials, weigh them according to the ratio and put them into a pressure-resistant bottle. Weigh trioctylphosphine oxide and put it into the pressure-resistant bottle. Then add anhydrous ethanol to obtain the first solution. (2) Add 1-octadecene to the first solution, treat the mixed solution with an ultrasonic machine, and obtain the second solution after the reaction solution is fully dissolved; (3) Place the second solution in an oil bath and heat it to 60~80℃ for 5~30 minutes to allow the nano-alloy to grow crystal nuclei. Then, react it at 140~220℃ for 20~60 minutes to allow the crystal nuclei to grow anisotropically into nano-medium and high entropy alloys, thus obtaining the third solution. (4) Transfer the third solution to a centrifuge tube, wash, centrifuge, and collect the precipitate to obtain the Fe-Co-Ni nano-alloy; The volume molar ratio of anhydrous ethanol, 1-octadecene, trioctylphosphine oxide, and the single element is 3~5 ml: 10 ml: 1 mmol: 1~2 mmol.
2. The Fe-Co-Ni nanoalloy according to claim 1, characterized in that, The nano-alloy has a nanocrystal size of 400~600nm; the nano-alloy is a two-dimensional nanosheet HCP single-phase structure, and the thickness of the nanosheet is 10~50nm.
3. The method for preparing Fe-Co-Ni nanoalloys according to claim 1, characterized in that, Includes the following steps: (1) Using chlorides or acetylacetones or acetates of iron, cobalt, nickel, manganese, copper and zinc as raw materials, weigh them according to the ratio and put them into a pressure-resistant bottle. Weigh trioctylphosphine oxide and put it into the pressure-resistant bottle. Then add anhydrous ethanol to obtain the first solution. (2) Add 1-octadecene to the first solution, treat the mixed solution with an ultrasonic machine, and obtain the second solution after the reaction solution is fully dissolved; (3) Place the second solution in an oil bath and heat it to 60~80℃ for 5~30 minutes to allow the nano-alloy to grow crystal nuclei. Then, react it at 140~220℃ for 20~60 minutes to allow the crystal nuclei to grow anisotropically into nano-medium and high entropy alloys, thus obtaining the third solution. (4) Transfer the third solution to a centrifuge tube, wash, centrifuge, and collect the precipitate to obtain the Fe-Co-Ni nano-alloy; The volume molar ratio of anhydrous ethanol, 1-octadecene, trioctylphosphine oxide, and the single element is 3~5 ml: 10 ml: 1 mmol: 1~2 mmol.
4. The method for preparing a Fe-Co-Ni nanoalloy according to claim 3, characterized in that, The purity of the chloride, acetylacetone, or acetate is above 99.5%.
5. The method for preparing Fe-Co-Ni nanoalloys according to claim 3, characterized in that, In step (2), the mixed solution is treated with an ultrasonic machine for more than 30 minutes until it is completely dissolved.
6. The method for preparing Fe-Co-Ni nanoalloys according to claim 3, characterized in that, In step (4), wash with a mixed solution of ethanol:acetone:cyclohexane 1~2:1:1, centrifuge at 4000~6000 rpm for 5~10 minutes, discard the solution and keep the precipitate; repeat the washing operation three or more times until the solution becomes clear and transparent, collect the precipitate and store it in cyclohexane solution at 4℃.
7. The application of the nanoalloys according to claim 1 or 2 in bioenzymes and high-temperature alloy devices.
8. The application according to claim 7, characterized in that, The bio-enzyme has the ability to catalyze hydrogen peroxide and can promote the generation and removal of reactive oxygen species. The application is not for diagnostic or therapeutic purposes.
Citation Information
Patent Citations
Preparation method and application of high-entropy nano-enzyme
CN113318733A
Synthesis method of multi-morphology cerium oxide nanoparticles
CN115703646A